The influence of location and coating on the development of an in-water grooming program to maintain ship hull coatings - Melissa Tribou; Geoffrey Swain; Harrison Gardner; Sam Royster; Jarema M. Didoszak; Dean Webster; Joseph Dahlgren (Biofouling, 2026)

Cellular senescence—from solid organs to vascularized composite allotransplants - Leonard Knoedler; Andreas Schroeter; Jasper Iske; Jillian Dean; Sam Boroumand; Thomas Schaschinger; Tobias Niederegger; Samuel Knoedler; Adriana C. Panayi; Max Heiland; Stefan G. Tullius; Bohdan Pomahac; et al. (GeroScience, 2025)
Vascularized composite allotransplantation (VCA) has emerged as a novel therapy approach to restore form and function in patients with severe tissue defects of the face, hand, and abdominal wall, among other anatomical regions. The composite allografts comprise different tissues such as skin, muscle, or bone. Clinical data demonstrate promising mid- and long-term outcomes following VCA surgery, but our understanding of the cellular interactions and molecular pathways in VCA surgery is oftentimes deduced from solid organ transplantation (SOT). In SOT, the concept of cellular senescence has grown increasingly popular which is characterized by a permanent cellular proliferation arrest in response to endogenous and exogenous stimuli. Senescent cells, through the release of mitochondrial DNA and secretion of proinflammatory proteins, can amplify the immunogenicity of transplants, hindering graft acceptance and longevity. This understanding has paved the way for novel interventions, including the use of senolytics—agents that selectively eliminate senescent cells—to modulate immune responses and mediate immunotolerance. There is a body of evidence that underlines the therapeutic potential of senescence to improve SOT outcomes; however, the relevance of senescence to VCA outcomes remains elusive. In this review, we aim to summarize the current literature on senescence in different solid organ transplants and outline the potential impact of senescence on VCA outcomes. This knowledge may help providers develop a broader understanding of the cellular and molecular landscape in VCA to develop targeted therapies and advance VCA patient care.

Exposure to toxic metal(loid)s via breastmilk and stunting in infants living in the Lake Atitlán watershed, Guatemala - Sandra Rodríguez Quintana; Frank A. von Hippel; Mónica Orozco; Noel Solomons; Dean Billheimer; Maria A. Sans-Fuentes; Mary Kay Amistadi; Sam Sneed; Paloma Beamer; Alejandra Zamora; Eileen Rivera; Ruth Forsten; et al. (Environmental Pollution, 2025)

Moving to a new normal: Analysis of shifting climate normals in New Zealand - Raghav Srinivasan; Trevor Carey‐Smith; Linda Wang; Andrew Harper; Sam Dean; Gregor Macara; Ruotong Wang; Stephen Stuart (International Journal of Climatology, 2024)
New Zealand's National Institute of Water and Atmospheric Research publishes climate normals for New Zealand that are used for reporting the regional state of the climate, climate extremes and variability. Temperature and precipitation patterns are affected by both anthropogenic climate change and natural climate variability which in turn affect the climatological normal values calculated every decade. This study investigates how New Zealand's normals for temperature and precipitation have shifted over time at the national, regional and seasonal scales from the 1941–1970 period to the 1991–2020 period. Contrary to WMO recommendations, but aligned with many other countries, New Zealand's climate normals have traditionally not undergone homogenisation. The impact of introducing some homogenisation in the latest 1991–2020 normals, in contrast to historical non‐homogenized station normals, has been assessed using a new homogenized “Seventeen‐Station” temperature series from 1941 to 2020. We demonstrate that interpolating sparse non‐homogenized normals spatially to a grid can produce significant erroneous patterns and therefore undermine the accuracy of the conclusions drawn when using such normals. We find that the historical non‐homogenized temperature normals have a consistent negative bias in the long‐term trend at national, regional and seasonal scales. Our analysis of homogeneity tested precipitation showed consistent decreases at a national scale across all normal periods relative to the 1951–1980 precipitation normal. We also highlight how fixed period temperature and precipitation normals do not fully reflect the current state of a climate that is influenced by decadal variability and global warming. To derive normals fit for use in a changing climate it is suggested that automated methods for broad data homogenisation be developed along with alternative methods to derive normals that account for a non‐stationary climate.